Covid-19 Pandemic Risk Awareness Among Secondary School Students - Ologele Ibrahim (IJORER : International Journal of Recent Educational Research, 2022)
The Coronavirus outbreak proved to be one of the most transformative events in the modern period. This study objectives are to investigate whether difference exist between knowledge of covid-19 risk and; (i) not use of nose mask, (ii) not observe social distance and, (iii) whether difference exist between Muslim and Christianity on awareness of Covid-19 risk in the study area. The population of the study comprised all secondary school students in the study area. The study adopted a descriptive research design of survey type and multi-stage sampling technique was used to select 266 respondents participated in the study. The findings of the study revealed that, the students have knowledge that no use of nose mask is a risk for contacting Covid-19 disease, students do not have knowledge that failure to observe social distance is a risk for contacting Covid-19 infection and there is no difference between Muslim and Christian students of their awareness on Covid-19 pandemic risk among secondary school students in the study area The researcher recommends among others that the Patigi local government educational authority should organize enlightenment programme for secondary school students that will educate them on the activities that can put them at the risk of contacting Covid-19 infection which is harmful to their health